Leadership for Innovation in Digital Teaching: A Meta-Analysis Review of Principals’ Influence on Teachers’ Innovative Work Behavior - Umalihayati; Fajari, Laksmi Evasufi Widi; Mutoharoh; Nuryati; Ma'arif, Minhatul (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to examine the overall effect of principals’ leadership on teachers’ innovative work behavior, compare the relative strength of different leadership styles, and assess heterogeneity and potential publication bias within the post-2015 digital education context. A meta-analysis of 26 quantitative studies (k = 26) indexed in Scopus between 2015 and 2025 was conducted using a random-effects model. The inclusion criteria were: (1) empirical quantitative studies; (2) examination of the relationship between principals’ leadership and teachers’ innovative work behavior; (3) provision of statistical data convertible into effect sizes; and (4) publication in Scopus-indexed journals. Statistical indicators (r, t, and F values) were converted into standardized effect sizes and analyzed using JASP to estimate pooled effects, heterogeneity indices, and publication bias statistics. The results indicate that (1) there is a very high level of heterogeneity across studies (I² > 98%); (2) all leadership styles demonstrate a positive and significant effect on teachers’ innovative work behavior (p < 0.001), with visionary leadership showing the largest effect size relative to participative, transformational, and ethical leadership styles (r = 0.641); and (3) publication bias tests using the Egger test and Fail-safe N reveal no significant indication of publication bias. These findings indicate that principals’ leadership is a significant factor in promoting teachers’ innovative work behavior in technology-mediated learning environments; however, the magnitude of its impact varies substantially across contextual conditions.